FIRST RECORD OF THE INVASIVE NILE TILAPIA Oreochromis niloticus (PERCIFORMES: CICHLIDAE) IN BANGKA ISLAND, INDONESIA - Destra Ramadhanu; Martin Yermias Luhulima; Raihan Aliefani Alfian; Agus Miftahudin Hafidz; Akhlakul Kanaah; Mustobi Prananda; Sekar Putri; Yordi Aprianto; Ramadhan Aryo Nugroho; Andika Saputra; Ari Sabri; Malik Abdul Azis; Dedi Sanjaya; Fitri Sil Valen; Puryoso Puryoso (Journal of Aquatropica Asia, 2023)
This study aims to report the presence of Tilapia Tilapia Oreochromis niloticus on Bangka Island (Indonesia) for the first time and update the invasion range of this species. Previously, this species had invaded various areas in Indonesia such as Sumatra, Java, and Sulawesi. The presence of Invasive Nila Tilapia can have a negative impact on aquatic biota through food competition, predation, and disease transmission. A total of 30 tilapia specimens were caught using Anco's fishing gear which was installed for 2 minutes consisting of mature and seeds, ranging in size from 20mm to 90mm in the Mang Kalok River, Rebo Village, Bangka Induk Regency, Bangka Island, Indonesia through a field expedition on June 11, 2023. A description of the morphological characters of the captured specimens is provided in the discussion.